STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP IT MUTIARA IRSYADI INDRAMAYU - Arifin (UNISAN JURNAL, 2023)
This study aims to find out several leadership styles that can be implemented by school principals. This research uses a qualitative method using a descriptive approach that seeks to understand the phenomenon of what is experienced by the research subject holistically. The results of the study show that the principal of an Islamic elementary school in District, North Jakarta already has competence in accordance with government regulations and has a good and ideal leadership style and supports teacher performance towards professionalism. Among the appropriate leadership styles that have been implemented is a democratic and participative leadership style, so that ideas and inspiration from teachers and education staff can be developed. Democratic and participatory leadership styles also provide opportunities to overcome various problems and find solutions together. This leadership style is also in accordance with Islamic religious teachings, forms a harmonious environment in the work environment and supports the improvement of teacher performance in schools.